Code Team Structure and Training in the Pediatric Resuscitation Quality International Collaborative. Issue 8 (August 2021) - Pfeiffer, Stephen; Lauridsen, Kasper Glerup; Wenger, Jesse; Hunt, Elizabeth A.; Haskell, Sarah; Atkins, Dianne L.; Duval-Arnould, Jordan M.; Knight, Lynda J.; Cheng, Adam; Gilfoyle, Elaine; Su, Felice; Balikai, Shilpa; et al.
Abstract : Objectives: Code team structure and training for pediatric in-hospital cardiac arrest are variable. There are no data on the optimal structure of a resuscitation team. The objective of this study is to characterize the structure and training of pediatric code teams in sites participating in the Pediatric Resuscitation Quality Collaborative. Methods: From May to July 2017, an anonymous voluntary survey was distributed to 18 sites in the international Pediatric Resuscitation Quality Collaborative. The survey content was developed by the study investigators and iteratively adapted by consensus. Descriptive statistics were calculated. Results: All sites have a designated code team and hospital-wide code team activation system. Code team composition varies greatly across sites, with teams consisting of 3 to 17 members. Preassigned roles for code team members before the event occur at 78% of sites. A step stool and backboard are used during resuscitations in 89% of surveyed sites. Cardiopulmonary resuscitation (CPR) feedback is used by 72% of the sites. Of those sites that use CPR feedback, all use an audiovisual feedback device incorporated into the defibrillator and 54% use a CPR coach. Multidisciplinary and simulation-based code team training is conducted by 67% of institutions. Conclusions: Code team structure, equipment, and training vary widely in a survey of international children's hospitals. The variations in team composition, role assignments, equipment, and training described in this article will be used to facilitate future studies regarding the impact of structure and training of code teams on team performance and patient outcomes. Abstract : Supplemental digital content is available in the text.